Checklist and phenetics studies of nymphs of two species of triatomines: Triatoma lenti Sherlock & Serafim, 1967 and Triatoma sherlocki Papa, Jurberg, Carcavallo, Cerqueira, Barata, 2002 (Hemiptera: Reduviidae: Triatominae) - Rosseto, Leandro Augusto [UNESP]; Paiva, Vinícius Fernandes De; Belintani, Tiago; Oliveira, Jader de; Mendonça, Vagner José; Rosa, João Aristeu Da [UNESP] (FapUNIFESP (SciELO), 2021)
INTRODUCTION: Triatoma lenti and Triatoma sherlocki are endemic species of the State of Bahia, located in northeastern Brazil, where they have records of domiciliation in the human environment. In view of the epidemiological aspect and taxonomic importance of these species for the systematics of the Triatoma genus, a study was carried out with nymphs of all five instars. METHODS: An extensive review of studies on nymphs from the subfamily Triatominae is presented. Morphology was studied using a scanning electron microscope and morphometric analyses. RESULTS: The morphological study allowed us to characterize and discriminate species by means of scanning electron microscope of the last abdominal segment. In addition, the results show morphometric variability, with the total size of the head that best discriminates the species. CONCLUSIONS: Studies on nymphs are fundamental to the ecosystem; however, the literature on the immature forms of certain groups is scarce, difficult to use, or nonexistent. Therefore, this study includes morphological and morphometric data of the nymphal instars of T. lenti and T. sherlocki, corroborating the specific taxonomy of these species.